All-trans retinoic acid in the treatment of pediatric acute promyelocytic leukemia. Issue 9 (September 2012) - Masetti, Riccardo; Vendemini, Francesca; Zama, Daniele; Biagi, Carlotta; Gasperini, Pietro; Pession, Andrea
Acute promyelocytic leukemia (APL) is a rare form of acute myeloid leukemia with specific epidemiological, pathogenetic and clinical features. Its frequency varies widely among nations, with a decreased incidence among 'Nordic' origin populations. The molecular hallmark of the disease is the presence of a balanced reciprocal translocation resulting in the PML/RAR-α gene fusion, which represents the target of the all- trans retinoic acid (ATRA) therapy. The introduction of ATRA in conjunction with anthracyclines marked a turning point in the treatment of APL, previously associated with a significant morbidity and mortality. Nowadays the standard front-line therapy for pediatric APL includes ATRA in every phase of the treatment, resulting in a complete remission rate of 90–95%. Here we provide an overview of the role of ATRA in the treatment of pediatric APL, summarizing the most relevant clinical results of recent decades and investigating future therapeutic perspectives for children with APL.